2022
DOI: 10.1111/bph.15791
|View full text |Cite
|
Sign up to set email alerts
|

Increased heroin intake and relapse vulnerability in intermittent relative to continuous self‐administration: Sex differences in rats

Abstract: Background and Purpose Studies using intermittent‐access drug self‐administration show increased motivation to take and seek cocaine and fentanyl, relative to continuous access. In this study, we examined the effects of intermittent‐ and continuous‐access self‐administration on heroin intake, patterns of self‐administration and cue‐induced heroin‐seeking, after forced or voluntary abstinence, in male and female rats. We also modelled brain levels of heroin and its active metabolites. Experimental Approach Rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 107 publications
1
16
1
Order By: Relevance
“…There is extensive evidence that the schedule of access engenders distinct behavioral phenotypes for cocaine self‐administration, and despite being understudied, there is evidence that this may be true for opioids as well. Indeed, a recent study found that IntA to heroin resulted in maintained seeking from abstinence day 1 to abstinence day 21 with no incubation 56 . Thus, in the current studies, rats may be expressing exaggerated seeking early in abstinence, which remains elevated later in abstinence, resulting in the absence of incubation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…There is extensive evidence that the schedule of access engenders distinct behavioral phenotypes for cocaine self‐administration, and despite being understudied, there is evidence that this may be true for opioids as well. Indeed, a recent study found that IntA to heroin resulted in maintained seeking from abstinence day 1 to abstinence day 21 with no incubation 56 . Thus, in the current studies, rats may be expressing exaggerated seeking early in abstinence, which remains elevated later in abstinence, resulting in the absence of incubation.…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, a recent study found that IntA to heroin resulted in maintained seeking from abstinence day 1 to abstinence day 21 with no incubation. 56 Thus, in the current studies, rats may be expressing exaggerated seeking early in abstinence, which remains elevated later in abstinence, resulting in the absence of incubation. Interestingly, our observation of robust oxycodone seeking both early and later in abstinence is consistent with what has been reported for human opioid craving, which is characterized by persistent opioid craving throughout abstinence and hence a lack of incubation of craving.…”
Section: Inta To Oxycodone Engenders Escalation Of Intake and Sustain...mentioning
confidence: 75%
“…However, not all studies report such differences (Lynch and Carroll, 1999; D’Ottavio et al, 2022). D’Ottavio et al (2022) found that females had increased incubation of heroin craving compared to males, but only after intermittent access, and not continuous access, heroin self-administration. Nonetheless, a recent comprehensive review surveying the field found that studies examining measures of opioid craving in rodents largely did not reveal sex differences (Nicolas et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…For example, George et al (2021) found that female rats displayed increased responding and intake across heroin doses following 6-h heroin self-administration. However, not all studies report such differences (Lynch and Carroll, 1999;D'Ottavio et al, 2022). D'Ottavio et al (2022 found that females had increased incubation of heroin craving compared to males, but only after intermittent access, and not continuous access, heroin self-administration.…”
Section: Female and Male Rats Self-administer Heroin Similarlymentioning
confidence: 99%
“…This is critical from a translational perspective given that other studies examining sex differences in opioid self-administration show inconsistent results. In this regard, most studies report higher rates of opioid self-administration in females compared to males [88][89][90][91][92][93][94][95][96][97][98][99][100] while others fail to capture any sex differences [99][100][101][102] . Notably, one study found that males self-administer more oxycodone when demand is low (FR1) and this modest effect was on the number of infusions obtain rather than lever responses, suggesting that males were only slightly more efficient during the 6-s timeout periods 103 .…”
Section: Discussionmentioning
confidence: 99%